KEDUDUKAN HARTA BERSAMA YANG DIJADIKAN OBJEK JAMINAN HAK TANGGUNGAN DALAM HUTANG PIUTANG DAN DIEKSEKUSI OLEH PENGADILAN (STUDI PUTUSAN NOMOR 13/PDT.BTH/2021/PN TJK) - Shafa Clarissha, Vindria; Ayu Hapsari, Recca; Hesti, Yulia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
Mortgage rights are regulated in Law Number four of 1996 concerning Mortgage Rights on Land and Objects Related to Land, hereinafter abbreviated as UUHT. With a variety of options 13/pdt.bth/2021/pn/tjk where the land due to the marriage is used as collateral for the rights of borrowing and borrowing through the husband and spouse as guarantors. election No.13/pdt.bth/2021/pn/tjk. The approach used in this study is empirical through interviews with judges at the Tanjung Karang District Court. Land rights that can be encumbered with Borrowing Rights consist of: Ownership Rights, Cultivation Rights, Building Use Rights, and Land Use Rights on state land which in accordance with the legal guidelines and guidelines of the winner must be registered and according to their nature can be transferred. Flats that stand on Ownership Rights, Building Use Rights and Use Rights granted through the state. Because one of the parties,namely Edwin Bunyamin Pohar,was not drawn as a party in the a quo rebuttal case,the rebuttal of the rebuttal as a rebuttal is lacking because not all parties in the main case are parties in the a quo rebuttal case, so the rebuttal of the rebuttal must be declared no acceptable (Niet Onvankelijke Verklaard).